The Relationship between Peer Assessment and Natural Science Learning Outcomes in Elementary Education - Jamilah (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to determine the relationship between peer assessment and science learning outcomes in elementary education. The research method used a correlational quantitative approach, involving 90 sixth-grade students. Data were collected through a validated questionnaire containing 38 items measuring four dimensions: understanding, participation, perceived benefits, and socio-emotional impacts. Data analysis was conducted using prerequisite tests (Shapiro-Wilk normality test and linearity test through ANOVA) and hypothesis testing using Pearson correlation. The results of the normality test indicate that the peer assessment data and science learning outcomes are both normally distributed. The linearity test confirmed a significant linear relationship between the two variables without significant deviations from linearity. The Pearson correlation test revealed a significant and strong positive relationship between peer assessment and science learning outcomes, indicating that the higher the peer assessment, the higher the science learning outcomes achieved. It can be concluded that peer assessment is effectively implemented at the elementary education level and can be integrated as a formative assessment strategy to improve science learning outcomes.